2014
DOI: 10.1002/elsc.201300159
|View full text |Cite
|
Sign up to set email alerts
|

Galanthamine biosynthesis in plant in vitro systems

Abstract: The Amaryllidaceae alkaloid galanthamine (Gal) is a long‐acting, selective, reversible, and competitive acetylcholinesterase inhibitor used for the treatment of early‐ to mid‐stage Alzheimer's disease, poliomyelitis, and other neurological diseases. Currently, Gal is produced by extraction from plants such as daffodils (Narcissus cultivar Carlthon), snowflake (Leucojum aestivum), “red‐tubed lily” (Lycoris radiata), and Ungernia victoria, and alternatively by chemical synthesis. Due to the increased demand by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 40 publications
(85 reference statements)
0
25
0
Order By: Relevance
“…These studies showed a clear correlation between alkaloid accumulation and a number of biological, chemical and physical factors. Among the biological factors, let's focus on the importance of cell differentiation . According to Stanilova et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies showed a clear correlation between alkaloid accumulation and a number of biological, chemical and physical factors. Among the biological factors, let's focus on the importance of cell differentiation . According to Stanilova et al.…”
Section: Introductionmentioning
confidence: 99%
“…These studies showed a clear correlation between alkaloid accumulation and a number of biological, chemical and physical factors. Among the biological factors, let's focus on the importance of cell differentiation [23,24]. According to Stanilova et al [25], galanthamine content in L. aestivum directly regenerated bulblets was 10 times greater than in L. aestivum callus-derived shoots (over 1 mg/g DW vs. 0.1 to 0.2 mg/g DW).…”
mentioning
confidence: 99%
“…Growth regulators significantly affect galanthamine biosynthesis by affecting cellular differentiation. However, as concluded by Berkov et al., growth regulators affect secondary metabolism differently in various in vitro cultures derived from the same plant . Their effect is specific to each individual culture.…”
Section: Resultsmentioning
confidence: 92%
“…4-O-methylnorbelladine is considered as a key intermediate. The biosynthesis of galanthamine involves the phenol oxidative coupling of O-methylnorbelladine, and then following further steps, galanthamine is produced [25].…”
Section: Biosynthesis Pathway Of Alkaloids: Different Facts In Cell Cmentioning
confidence: 99%